2022
DOI: 10.3390/medicina58121716
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MRI Features of Breast Cancer Molecular Subtypes

Abstract: Background and Objectives: Breast cancer (BC) molecular subtypes have unique incidence, survival and response to therapy. There are five BC subtypes described by immunohistochemistry: luminal A, luminal B HER2 positive and HER2 negative, triple negative (TNBC) and HER2-enriched. Multiparametric breast MRI (magnetic resonance imaging) provides morphological and functional characteristics of breast tumours and is nowadays recommended in the preoperative setting. Aim: To evaluate the multiparametric MRI features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…One study where tumors were segmented on DWI and segmentation ROIs were propagated onto ADC maps reported high accuracy in predicting hormonal status and some molecular types such as luminal B [ 21 , 22 ]. In addition, Leithner et al [ 21 ] reported better results when first-order histogram parameters were obtained from ADC maps.…”
Section: Discussionmentioning
confidence: 99%
“…One study where tumors were segmented on DWI and segmentation ROIs were propagated onto ADC maps reported high accuracy in predicting hormonal status and some molecular types such as luminal B [ 21 , 22 ]. In addition, Leithner et al [ 21 ] reported better results when first-order histogram parameters were obtained from ADC maps.…”
Section: Discussionmentioning
confidence: 99%
“…26 Although such immunohistochemical subtypes are determined by histopathological sampling, efforts have been made to predict different subtypes on imaging, often using a multiparametric approach. 10,[27][28][29][30] Angiogenesis and metabolism are the 2 hallmarks of cancer that can be evaluated by contrast-enhanced MRI and 18 F-FDG PET. 31 Proliferation can be assessed by DWI, 20 and the increase in metabolism that precedes proliferation can be used as an early marker of tumor growth.…”
Section: Subtype Angiogenesis Metabolism and Tumor Microenvironment R...mentioning
confidence: 99%
“…However, multiparametric data are now also used to tackle more complex tasks such as predicting subtypes and treatment response after neoadjuvant treatment. We have summarized selected recent research investigating the prediction of subtypes 10,27,29,30,91,[103][104][105][106][107][108][109] (Table 2), response after neoadjuvant treatment [110][111][112] (Table 3), and evaluating TILs or CAF [113][114][115][116] (Table 4) to provide an overview of the trends in parameters and methods used for analysis. The most popular combinations of imaging include DCE, DWI (ADC value), and T2WI.…”
Section: Multiparametric Approaches To Breast Cancer: Recent Advancesmentioning
confidence: 99%
See 2 more Smart Citations